Identification of a de novo mutation in KRT5 gene underlying epidermolysis bullosa simplex by whole exome sequencing in a Vietnamese patient - Thuong, Ma Thi Huyen; Truong, Dang Tien; Ha, Nguyen Hai; Ton, Nguyen Dang (Vietnam Journal of Biotechnology, 2021)
Epidermolysis bullosa simplex (EBS) is a group of epidermolysis bullosa (EB) and accounts for 75-85% EB cases. Most EBS patients are caused by mutations in KRT5 or KRT14, encoding for keratin 5 and keratin 14, respectively, which impair the structural entirety of paired intermediate filaments expressed in the fracture of basal keratinocytes and subsequent blistering of the epithelium. This study aimed to identify the causative mutation in a Vietnamese EB case. Whole exome sequencing (WES) was performed in the affected individual and revealed a de novo heterozygous pathogenic mutation in exon 7 of KRT5 gene, resulting in an amino acid change at position 477, with glutamic acid to lysine substitution (p.E477K). The KRT5 p.E477K was strong associated with the very severe or lethal of generalized severe EBS (GS-EBS), characterized by the severe symptoms at birth, improving with age and evolution to palmoplantar keratoderma and nail dysplasia. Our finding will aid the molecular diagnosis, prognosis prediction of the patient with GS-EBS due to p.E477K and significant genetic counselling the family concerning the recurrence risk for future pregnancies.